Objective Structured Video Examination (OSVE) Toolkit for Teaching and Assessing the ACGME Competencies (Out of Print) - Deborah Simpson (Association of American Medical Colleges, 2006)
Abstract The Objective Structured Video Examination (OSVE) Toolkits are a set of 18-36 self-contained resources to use for teaching and assessing the ACGME competencies with primary foci on systems-based management, practice-based learning and improvement, and communication and interpersonal skills, using geriatrics as the underlying content area. Each OSVE tool consists of four components: an instructor guide; an assessment tool; a video trigger; and a scoring key. The unique feature of these tools is that each is centered around a short (1-3 minutes) video. For example, one trigger shows Mrs. Tang, a 78 year old Japanese American female, who is in for a follow-up posthip surgery clinic visit and her records are missing. Residents are asked questions about how to access records in a short period of time and exercise. Completed tools were piloted in a variety setting (e.g., rounds, morning report). Time to complete each toolkit is approximately 15-20 minutes including scoring time. The OSVE Toolkit is compact and easy to access. All materials come to you on one CD, individualized by ACGME competency or clinical topic.